Anorganska kemija: Navodila za laboratorijske vaje - Gyergyek, Sašo (2023)
Inorganic Chemistry: Laboratory Manual. Laboratory manual for Inorganic chemistry course for students attending Inorganic chemistry. The course is for students in 1st year of master level in Chemistry.
Keywords: inorganic chemistry; solid-state synthesis; precipitation; X-ray powder diffraction; magnetic measurements